2007
DOI: 10.1371/journal.ppat.0030004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Derived Dendritic Cells trans-Infect CD4 T Cells Primarily with Surface-Bound HIV-1 Virions

Abstract: In the prevailing model of HIV-1 trans-infection, dendritic cells (DCs) capture and internalize intact virions and transfer these virions to interacting T cells at the virological synapse. Here, we show that HIV-1 virions transmitted in trans from in vitro derived DCs to T cells principally originate from the surface of DCs. Selective neutralization of surface-bound virions abrogated trans-infection by monocyte-derived DCs and CD34-derived Langerhans cells. Under conditions mimicking antigen recognition by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
150
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(156 citation statements)
references
References 28 publications
5
150
1
Order By: Relevance
“…A recent report concluded that primarily cell-surfacebound HIV-1 is transferred to T cells (40), whereas previous studies have shown that mainly the internalized virus is transferred (37). These latter reports demonstrated that, although a large part of the virus is degraded in lysosomes (27,28), part of the virus recycles to infectious synapse (41,42) or exosomes (43).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report concluded that primarily cell-surfacebound HIV-1 is transferred to T cells (40), whereas previous studies have shown that mainly the internalized virus is transferred (37). These latter reports demonstrated that, although a large part of the virus is degraded in lysosomes (27,28), part of the virus recycles to infectious synapse (41,42) or exosomes (43).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 transmission in cis is characterized by direct infection of the DC, which takes a few days, resulting in transfer of de novo-produced virions (9,10). DC-mediated HIV-1 transmission in trans relies on the capture of HIV-1 particles, followed by transfer to HIV-1-susceptible CD4 cells.…”
mentioning
confidence: 99%
“…DC-mediated HIV-1 transmission in trans relies on the capture of HIV-1 particles, followed by transfer to HIV-1-susceptible CD4 cells. Typically, trans-infection starts within a few hours following capture and can continue for a few days (9,11). Transmission of HIV-1 from DCs to CD4 + T lymphocytes occurs via formation of a virological synapse upon cell-cell contact (12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that HIV-1 takes advantage of a pre-existing exosome Ag-dissemination pathway intrinsic to mDC to enable final trans-infection of CD4 + T cells (10)(11)(12), whereas others investigators adduce that only DC surface-bound HIV-1 are able to trans-infect target cells (13). However, both models have been reconciled, demonstrating that LPS-matured DC (mDC LPS) concentrate HIV-1 in a tetra-spanin-rich compartment that remains physically connected to the extracellular milieu (9).…”
mentioning
confidence: 99%